STATE OF ANTIOXIDANT DEFENCE OF THE SPLEEN PARENCHYMA OF RATS UNDER THE INFLUENCE OF A COMPLEX OF CHEMICAL FOOD ADDITIVES - Bilash, S.M.; Mamai, O.V.; Pronina, O.M.; Koptev, M.M.; Pirog-Zakaznikova, A.V.; Oliinichenko, Ya.O.; Kolomiiets, S.V. (World of Medicine and Biology, 2025)
The study is aimed at analysing the effect of a complex of food additives (sodium glutamate, sodium nitrite, ponceau 4R) on the state of the antioxidant system of the rat spleen. The experiment was carried out on 70 white rats, which were administered a mixture of food additives in doses below the maximum permissible doses for 1–20 weeks. The biphasic dynamics of antioxidant enzyme activity was established: an initial moderate decrease in catalase and superoxide dismutase activity at 4–8 weeks, followed by a multidirectional imbalance at 12–20 weeks (a sharp increase in catalase activity against a significant decrease in superoxide dismutase activity). The detected disbalance in the system of enzymatic antioxidant defence reflects the development of oxidative stress in the spleen tissues under prolonged exposure to food additives, which can lead to impaired immunological function of the organ and be one of the links in the pathogenesis of the systemic toxic effects of the studied substances.